Permasalahan Sosial Pada Masyarakat - Tutesa; Yossita Wisman (FKIP, Universitas Palangka Raya, 2020)
Social inequality is a state of social imbalance in society that makes a very striking difference. In terms of social inequality, it is very clear from various aspects, for example in the aspect of justice it can occur. Between rich and poor people are very differentiated in any aspect, villagers who migrate to the city are also affected by this, it is true to say that